2008
DOI: 10.1143/apex.1.101901
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Switching Capability on Bipolar Resistance Switching Device with Ta/Pr0.7Ca0.3MnO3/Pt Structure

Abstract: We found that Pr0.7Ca0.3MnO3 (PCMO) film sandwiched by a Ta top electrode (TE) and a Pt bottom electrode (BE) exhibited bipolar resistance switching similar to that of Ti(TE)/PCMO/Pt(BE). The switching capability of Ta/PCMO/Pt was greatly improved by pulse-forming compared to dc-forming, which are both pre-treatments to enable resistance switching by pulsed voltage. Switching speeds faster than 100 ns and rewrite cycles of more than 10,000 were obtained while maintaining a ratio of resistance change larger tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
36
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 17 publications
4
36
1
Order By: Relevance
“…The current knowledge of the microscopic details of these processes is still very limited, being also strictly dependent on the chosen materials and the fabrication protocols. For example, the choice of oxidizable electrodes like Al, Ti or Ta and the occurrence of rectifying current-voltage characteristics appear to be essential prerequisites for a typical resistive switching electrode-manganite-electrode device [56][57][58].…”
Section: Metal-oxide Interfaces In Resistive Switching Devicesmentioning
confidence: 99%
“…The current knowledge of the microscopic details of these processes is still very limited, being also strictly dependent on the chosen materials and the fabrication protocols. For example, the choice of oxidizable electrodes like Al, Ti or Ta and the occurrence of rectifying current-voltage characteristics appear to be essential prerequisites for a typical resistive switching electrode-manganite-electrode device [56][57][58].…”
Section: Metal-oxide Interfaces In Resistive Switching Devicesmentioning
confidence: 99%
“…Recently, there have been several reports that some metal materials are easily oxidized and reduced when they are used as top electrodes (TEs), which are involved in the growth and dissolution of metallic filaments during RS. [11][12][13] In our previous report, we observed that the oxidation of the active metal electrode (Al, Ti, Ta, etc.) and the reduction of some pervoskite oxides, such as Pr 0.7 Ca 0.3 MnO 3 (PCMO), at the interface will lead to RS behavior in the TE/PCMO/Pt structure but not for nonreactive metals (Pt, Ag, Au).…”
mentioning
confidence: 98%
“…and the reduction of some pervoskite oxides, such as Pr 0.7 Ca 0.3 MnO 3 (PCMO), at the interface will lead to RS behavior in the TE/PCMO/Pt structure but not for nonreactive metals (Pt, Ag, Au). 13 Therefore, it is clear that the RS effect is related to the formation and dissociation of such interfacial metal oxide layers that are involved as part of the conducting path. However, both filamentary and homogenous switching at the TE-oxide interface has been reported to coexist in one sample, exhibiting the opposite switching behavior.…”
mentioning
confidence: 99%
See 2 more Smart Citations